Wavelet analysis for Mueller matrix images of biological crystal networks - Ushenko, Yu.O.; Tomka, Yu.Ya.; Pridiy, O.G.; Motrich, A.V.; Dubolazov, O.V.; Misevitch, I.Z.; Istratiy, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
Theoretically grounded in this work is the efficiency of using the statistical and
fractal analyses for distributions of wavelet coefficients for Mueller-matrix images of
biological crystal networks inherent to human tissues. The authors found interrelations
between statistical moments and power spectra for distributions of wavelet coefficients
as well as orientation-phase changes in networks of biological crystals. Also determined
are criteria for statistical and fractal diagnostics of changes in the birefringent structure of
biological crystal network, which corresponds to pathological changes in tissues.